2020
DOI: 10.1113/jp280378
|View full text |Cite
|
Sign up to set email alerts
|

A single, clinically relevant dose of the GABAB agonist baclofen impairs visuomotor learning

Abstract: Baclofen is a GABA B agonist prescribed as a treatment for spasticity in stroke, brain injury and multiple sclerosis patients, who are often undergoing concurrent motor rehabilitation. r Decreasing GABAergic inhibition is a key feature of motor learning and so there is a possibility that GABA agonist drugs, such as baclofen, could impair these processes, potentially impacting rehabilitation. r Here, we examined the effect of 10 mg of baclofen, in 20 young healthy individuals, and found that the drug impaired r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 55 publications
3
8
0
Order By: Relevance
“…Besides these discrepancies, our findings in the mature participants suggest that lower GABA concentration within the IPS is associated with enhanced visuomotor processing, thus extending the involvement of GABA in the acquisition of visuomotor abilities. In addition to our suggestion of the involvement of developmental GABA in visuomotor processing, administration of GABA B agonist baclofen was shown to impair visuomotor processing in healthy adults (60). Consistent with this, we showed here that elevated GABA levels in the IPS are associated with poor visuomotor processing in later developmental stages.…”
Section: Visuomotor Processing Is Associated With Ips Glutamate and G...supporting
confidence: 89%
“…Besides these discrepancies, our findings in the mature participants suggest that lower GABA concentration within the IPS is associated with enhanced visuomotor processing, thus extending the involvement of GABA in the acquisition of visuomotor abilities. In addition to our suggestion of the involvement of developmental GABA in visuomotor processing, administration of GABA B agonist baclofen was shown to impair visuomotor processing in healthy adults (60). Consistent with this, we showed here that elevated GABA levels in the IPS are associated with poor visuomotor processing in later developmental stages.…”
Section: Visuomotor Processing Is Associated With Ips Glutamate and G...supporting
confidence: 89%
“…Second, it is well-established that the central nervous system includes at least two distinct forms of GABAergic inhibition: a tonic one involving (mostly extrasynaptic) metabotropic GABA A receptors, and a phasic one involving (mostly intrasynaptic) ionotropic GABA B receptors. Although resting MRS-GABA signal is thought to predominantly reflect the former ( Stagg, Bestmann, Constantinescu, Moreno Moreno, Allman, Mekle, Woolrich, Near, Johansen-Berg, Rothwell, 2011 , Stagg, Best, Stephenson, O’Shea, Wylezinska, Kincses, Morris, Matthews, Johansen-Berg, 2009 ), the latter may also explain some of the inter-individual variance in signal, and is known to play a role in adaptation memory ( Johnstone et al., 2021 ). The extent to which tonic versus phasic GABAergic signalling contributes to our findings therefore remains an open question for future research.…”
Section: Limitationsmentioning
confidence: 99%
“…Several studies have previously reported a correlational link between high GABA concentration, 27 or receptor activity, 28,29 and worse functional outcomes from rehabilitation post-stroke. Furthermore, a single dose of the GABA B agonist baclofen impairs aspects of motor learning in healthy humans 30 ; and GABA antagonists can improve post-stroke motor recovery in rats. 13,14 Given these findings, and another early retrospective study finding a negative impact of benzodiazepine prescription on motor function recovery 16 (though see Hesse and Werner 31 ), caution has previously been advised in the prescription of GABA agonists, particularly benzodiazepines, post-stroke.…”
Section: Discussionmentioning
confidence: 99%